The Determinants of Taxpayer Compliance with Tax Awareness as a Mediation and Education for Moderation - Hardiningsih, Pancawati; Januarti, Indira; Oktaviani, Rachmawati Meita; Srimindarti, Ceacilia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
This study aims to analyze the effects of tax knowledge, tax sanctions, and tax socialization on taxpayer compliance, as mediated and moderated by taxpayer awareness level of taxpayer education, respectively. The research sample included 196 taxpayers registered in the Primary South Semarang Tax Office. They were selected using the convenience sampling method. The data analysis employed structural equation modeling with warp partial least square. Results show that tax knowledge, tax sanctions, and tax socialization all have a significant positive effect on taxpayer awareness and taxpayer compliance. Meanwhile, the level of education does not moderate tax knowledge on taxpayer compliance. The taxpayers’ awareness mediates the relationship between tax compliance, on the one hand, and tax knowledge, tax socialization, and tax sanctions on the other hand. Thus, the Directorate General of Taxes must increase the intensity of guidance provided to taxpayers to encourage better compliance and reduce tax avoidance behaviors. Keywords : Tax knowledge; tax sanctions; tax dissemination; taxpayer awareness; taxpayer compliance.